CFD - analys av atriet i Kirunas nya stadshus - Nyberg, Marcus (2015)
LKAB:s mining of iron ore deep down underground is causing movements and subsidence which affects the buildings in central Kiruna. It has therefore been determined that the city of Kiruna in the next few years will be relocated and rebuilt. Kiruna municipality announced, in connection with the publication of the city movement, an architectural competition regarding the construction of their new city hall. The winning entry was created by a Danish firm called Henning Larsen Architects who chose to cooperate with the constructors at WSP:s office in Luleå.In this thesis a study is conducted of the atrium located inside of the city hall where the climate is studied by CFD simulations (computer-aided fluid analysis). In the study, climate analyzes are limited to six extreme cases where the temperature distribution, pressure distribution and air velocity are described. Simulations are performed at steady state and mass balance. Variables with transient behavior have not been taken into consideration.The results show that a general behavior appears in zones related to the stage and restaurant. In these zones the air velocity is at a critical level compared to stated criteria. Temperature criteria are exceeded while the heat from maximum amount of people is applied at entry level during conditions corresponding to a hot summer day. Validerat; 20150626 (global_studentproject_submitter)